Pengaruh Perubahan Leverage pada Manajemen Laba - Andy Surya Dharma, S. Agus; Wirama, Dewa Gede (E-Jurnal Akuntansi; Vol 30 No 6 (2020), 2020)
This research analyses the effect of changes in leverage on earnings management. Changes in leverage are changes in debt-to-equity ratio from previous years, and earnings management is measured by discretionary accruals estimated by the Modified Jones Model. Return to equity, net profit margin, company size, return on assets, and the level of leverage are treated as control variables. They are identified from the results of previous researches. The research population is nonfinancial companies listed in the Bursa Efek Indonesia in 2018. Sample size is calculated using the Slovin Formula, resulted in 225 companies in the sample which is further randomly stratified. Data were analyzed by multiple regression technique. Contrary to the hypothesis, changes in leverage are negatively affect earnings management. The result was probably caused by the fact that companies with improving leverage have much higher level of leverage than companies with worsening leverage from the previous year. Keywords: Agency Theory; Earnings Management; Leverage Change.